2015
DOI: 10.1161/jaha.115.002408
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vegetarian Diets on Blood Lipids: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials

Abstract: BackgroundVegetarian diets exclude all animal flesh and are being widely adopted by an increasing number of people; however, effects on blood lipid concentrations remain unclear. This meta‐analysis aimed to quantitatively assess the overall effects of vegetarian diets on blood lipids.Methods and ResultsWe searched PubMed, Scopus, Embase, ISI Web of Knowledge, and the Cochrane Library through March 2015. Studies were included if they described the effectiveness of vegetarian diets on blood lipids (total cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
198
1
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(225 citation statements)
references
References 50 publications
(169 reference statements)
12
198
1
14
Order By: Relevance
“…A recent meta-analysis that included 11 randomized trials, conducted on participants who followed vegetarian diets versus those who followed control diets, reported a significant lowering of total cholesterol, LDL cholesterol, and high-density lipoprotein cholesterol levels but not triglyceride levels. 24 Nevertheless, literature on the beneficial effects of VDs on triglyceride levels is inconsistent and contrasting. 7 Some studies reported the beneficial effects of VDs on triglyceride levels, whereas others did not observe any significant effect.…”
Section: Original Research Articlementioning
confidence: 99%
“…A recent meta-analysis that included 11 randomized trials, conducted on participants who followed vegetarian diets versus those who followed control diets, reported a significant lowering of total cholesterol, LDL cholesterol, and high-density lipoprotein cholesterol levels but not triglyceride levels. 24 Nevertheless, literature on the beneficial effects of VDs on triglyceride levels is inconsistent and contrasting. 7 Some studies reported the beneficial effects of VDs on triglyceride levels, whereas others did not observe any significant effect.…”
Section: Original Research Articlementioning
confidence: 99%
“…In their review, Ferdowsian and Barnard demonstrated that individuals consuming more plant foods have lower total cholesterol (TC) and low‐density lipoprotein cholesterol (LDL‐C) concentrations compared to those following diets that include more animal products. Furthermore, reviews by Wang et al and Yokoyama et al showed a lowering effect of vegetarian diets on TC, high‐density lipoprotein cholesterol (HDL‐C) and LDL‐C. No remarkable effect was found on triglyceride concentrations .…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of studies of plant‐based diets in the Ferdowsian and Barnard () study were associated with a reduction in TAG while the Wang et al . () study of vegetarian diets was not significant overall.…”
Section: Cardiovascular Risk Factors and Plant‐based Dietsmentioning
confidence: 81%
“…There is evidence from both RCTs and observational studies that those following plant‐based dietary regimes have improved blood lipid profiles, including lower levels of TC and LDL‐C (Wang et al . ; Dinu et al . ), and reduced BP and inflammatory and endothelial markers (Ruiz‐Canela et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation